2015
DOI: 10.1523/jneurosci.3093-13.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Prefrontal Cortex Achieves Inhibitory Control by Facilitating Subcortical Motor Pathway Connectivity

Abstract: Communication between the prefrontal cortex and subcortical nuclei underpins the control and inhibition of behavior. However, the interactions in such pathways remain controversial. Using a stop-signal response inhibition task and functional imaging with analysis of effective connectivity, we show that the lateral prefrontal cortex influences the strength of communication between regions in the frontostriatal motor system. We compared 20 generative models that represented alternative interactions between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
225
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(242 citation statements)
references
References 53 publications
16
225
1
Order By: Relevance
“…In fact, a recent study demonstrated that the prefrontal cortex may achieve inhibitory control by influencing frontostriatal circuits (Rae et al, 2015), which are known to participate in action selection (Seo et al, 2012). We suggest theta oscillations may be a mechanism through which this is achieved.…”
Section: Frontal Theta Oscillationsmentioning
confidence: 71%
“…In fact, a recent study demonstrated that the prefrontal cortex may achieve inhibitory control by influencing frontostriatal circuits (Rae et al, 2015), which are known to participate in action selection (Seo et al, 2012). We suggest theta oscillations may be a mechanism through which this is achieved.…”
Section: Frontal Theta Oscillationsmentioning
confidence: 71%
“…A recent effective connectivity study showed that rIFG modulates the excitatory influence between the pre-SMA and subthalamic nucleus (Rae, Hughes, Anderson, & Rowe, 2015). Consistent with the idea that response inhibition requires online maintenance of relevant information, rIFG has also been implicated in storing behaviorally relevant information in memory (Spitzer, Goltz, Wacker, Auksztulewicz, & Blankenburg, 2014;Marklund & Persson, 2012;Clark et al, 2007).…”
Section: Role Of Inferior Frontal Cortex In Processing Feedback In Acmentioning
confidence: 73%
“…These inter-species differences might reflect distinct electrophysiological recording context (e.g., the spatial sampling of STN during extracellular recordings is generally weak in humans), inter-species differences regarding STN connectivity with the prefrontal cortex (Astafiev et al, 2003) or a different implementation of inhibitory control signals in the human prefrontal cortex that would impact basal ganglia activities (Wessel & Aron, 2015). On a related note, thalamic and pedunculopontine nucleus projections to the STN could be the substrate for the very quick STN response observed in rat (Schmidt et al, 2013), while STN activity in humans could be driven by a slower prefrontalsubthalamic pathway (originating in the pre-SMA or in the inferior frontal gyrus, see Rae, Hughes, Anderson, Rowe, & Rowe, 2015).…”
Section: Stn Neuronal Activity During Stoppingmentioning
confidence: 99%